Reduced Endoplasmic Reticulum Luminal Calcium Links Saturated Fatty Acid-Mediated Endoplasmic Reticulum Stress and Cell Death in Liver Cells - Wei, Yuren (2009)
Chronic exposure to elevated free fatty acids, in particular long chain saturated fatty acids, provokes endoplasmic reticulum (ER) stress and cell death in a number of cell types. The perturbations to the ER that instigate ER stress and activation of the unfolded protein in response to fatty acids in hepatocytes have not been identified. The present study employed H4IIE liver cells and primary rat hepatocytes to examine the hypothesis that saturated fatty acids induce ER stress via effects on ER luminal calcium stores. Exposure of H4IIE liver cells and primary hepatocytes to palmitate and stearate reduced thapsigargin-sensitive calcium stores and biochemical markers of ER stress over similar time courses (6h). These changes preceded cell death, which was only observed at later time points (16h). Co-incubation with oleate prevented the reduction in calcium stores, induction of ER stress markers and cell death observed in response to palmitate. Inclusion of calcium chelators, BAPTA-AM or EGTA, reduced palmitate- and stearate-mediated enrichment of cytochrome c in post-mitochondrial supernatant fractions and cell death. These data suggest that redistribution of ER luminal calcium contributes to long chain saturated fatty acid-mediated ER stress and cell death.